1995
DOI: 10.1007/bf00003940
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-induced development of the ice-ice disease of the farmed red algae Kappaphycus alvarezii and Eucheuma denticulatum (Solieriaceae, Gigartinales, Rhodophyta)

Abstract: The most common perception of unfavorable environmental factors causing the ice-ice disease in the farmed seaweeds, Kappaphycus and Eucheuma, was demonstrated in this study for the first time using stressful conditions of abiotic factors in a continuous culture system. Light intensity of less than 50 /mol photon m -2 s-1 and salinity of 20%o or less induced ice-ice whitening characterized by short segments at midbranches which were similar to those observed in the Philippine seaweed farms, while temperatures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 5 publications
2
42
0
4
Order By: Relevance
“…Subsequent studies have examined and identified the abiotic factors that contribute to disease emergence, causative organisms and seasonality of disease outbreak (Largo et al 1995;Vairappan and Chong 2006). However, the dynamics of biofoulers on the culture lines and their possible resistance towards the "iceice" disease bacteria has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies have examined and identified the abiotic factors that contribute to disease emergence, causative organisms and seasonality of disease outbreak (Largo et al 1995;Vairappan and Chong 2006). However, the dynamics of biofoulers on the culture lines and their possible resistance towards the "iceice" disease bacteria has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…(HP0205UMS), Streptococcus sp. (HP0305UMS), Citrobacter freundii (HP0405UMS), Escherichia coli (SP0505UMS) and Klebsiella pneumoniae (HP0605UMS)Bacteria from diseased seaweed were isolated and identified using modified media and techniques described by Largo et al (1995), and Vairappan and Chong (2006). Meanwhile, the human pathogenic bacteria were obtained from Department of Pathology, Queen Elizabeth Hospital, Kota Kinabalu, Sabah.…”
Section: Antibacterial Bioassaymentioning
confidence: 99%
“…Vairappan et al (2008) comment that this disease was first reported in the Philippines by Trono (1974) being further related to unfavorable environmental factors in cultivation sites by Uyenco et al (1981). It was reported that Vibrio-Aeromonas and the Cytophaga-Flavobacterium complexes were responsible for inducing the "ice-ice" disease in individuals exposed to high temperature, low salinity, and irradiance (Largo et al 1995a(Largo et al , b, 1997(Largo et al , 1998.…”
Section: Introductionmentioning
confidence: 97%
“…The cause of 'ice-ice' is not well understood but there has been a general consensus that 'ice-ice' is due to physical and chemical stresses (Uyenco et al, 1981;Largo et al, 1995;Mtolera, 1996). High 'ice-ice' occurrence was observed at Kibuyuni from November to January, coinciding with the period of high temperature and salinity.…”
Section: Discussionmentioning
confidence: 98%